Six Motives of Polygamists in Indonesia - Ediz, M. Hidayat; Khairat, Hanivatul; Dasrizal, Dasrizal; Hasnah, Deliza Nur; Datres, Datres; Rahmat, Aulia; Sulastri, Widia; Zulfadli, Zulfadli (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
One of the important aspects to understand about the issue of polygamy is the motives of the perpetrators, as polygamy has psychological impacts on the wives and children involved. This study aims to explore the motives of polygamists and the effects on their wives and children. A qualitative method with a phenomenological approach was employed, and data were collected through in-depth individual interviews with five informants selected using purposive sampling. The six informants in this study are individuals who have two wives. All data were analyzed thematically using the Miles and Huberman analysis technique. The findings revealed six key motives of polygamists: i) the ability to be fair, ii) having sufficient economic resources, iii) the first wife suffering from a chronic illness, iv) hypersexual behavior, v) incompatibility between the first wife and the family, and vi) raising the dignity of the second wife due to economic hardship. These six motives challenge the negative perceptions of polygamists often held by society, which tend to view their actions as inherently wrong. In reality, these motives are driven by good intentions and align with the values of being a good Muslim.